From Green Super Rice to green agriculture: Reaping the promise of functional genomics research - Yu, Sibin; Ali, Jauhar; Zhou, Shaochuan; Ren, Guangjun; Xie, Huaan; Xu, Jianlong; Yu, Xinqiao; Zhou, Fasong; Peng, Shaobing; Ma, Liangyong; Yuan, Dingyang; Li, Zefu; et al. (Elsevier, 2022)
Producing sufficient food with finite resources to feed the growing global population while having a smaller impact on the environment has always been a great challenge. Here, we review the concept and practices of Green Super Rice (GSR) that have led to a paradigm shift in goals for crop genetic improvement and models of food production for promoting sustainable agriculture. The momentous achievements and global deliveries of GSR have been fueled by the integration of abundant genetic resources, functional gene discoveries, and innovative breeding techniques with precise gene and whole-genome selection and efficient agronomic management to promote resource-saving, environmentally friendly crop production systems. We also provide perspectives on new horizons in genomic breeding technologies geared toward delivering green and nutritious crop varieties to further enhance the development of green agriculture and better nourish the world population.